2008
DOI: 10.1017/s0022112008001390
|View full text |Cite
|
Sign up to set email alerts
|

The three-dimensional transition in the flow around a rotating cylinder

Abstract: The flow around a circular cylinder rotating with a constant angular velocity, placed in a uniform stream, is investigated by means of two- and three-dimensional direct numerical simulations. The successive changes in the flow pattern are studied as a function of the rotation rate. Suppression of vortex shedding occurs as the rotation rate increases (>2). A second kind of instabilty appears for higher rotation speed where a series of counter-clockwise vortices is shed in the upper shear layer. Three-dimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 22 publications
1
48
0
Order By: Relevance
“…At low rotation rates, α < 1, Akoury et al (2008) found that Mode A becomes unstable at higher Reynolds numbers as α is increased. At higher rotation rates, the flow becomes increasingly unstable to perturbations at Re = 200 in the range 3 α 5 (Meena et al 2011).…”
Section: Introductionmentioning
confidence: 93%
“…At low rotation rates, α < 1, Akoury et al (2008) found that Mode A becomes unstable at higher Reynolds numbers as α is increased. At higher rotation rates, the flow becomes increasingly unstable to perturbations at Re = 200 in the range 3 α 5 (Meena et al 2011).…”
Section: Introductionmentioning
confidence: 93%
“…One question of interest is whether this mode-switching signature of the upper branch still prevails when the cylinder is undergoing forced vibration. Indeed, the action of rotating fixed cylinders modifies the wake stability, whether the rotation is oscillatory (Tokumaru & Dimotakis 1991;Lo Jacono et al 2010;D'Adamo, Godoy-Diana & Wesfreid 2015) or uniform (El Akoury et al 2008;Rao et al 2013Rao et al , 2015. Thus, given that the cylinder is under uniform rotation, hence biasing the vorticity production towards one side and therefore biasing the wake topology, the question of how this affects the wake dynamics of the upper branch is of interest.…”
Section: Wake Structuresmentioning
confidence: 99%
“…Over a small range of α 4 there is a secondary region of wake unsteadiness, comprising low-frequency one-sided vortices, as shown by Mittal & Kumar (2003), Stojković et al (2003) and Pralits, Brandt & Giannetti (2010). Numerical simulations have shown that the critical Reynolds number of the secondary instability associated with the spanwise undulation of the von Kármán vortices increases with Reynolds number (El Akoury et al 2008;Rao et al 2015). Depending on α and Re, there exist a number of steady and unsteady wake modes (Pralits, Giannetti & Brandt 2013;Rao et al 2013Rao et al , 2015.…”
mentioning
confidence: 99%
“…However, this problem has important applications in designing several heat transfer devices used in modern industry. Al though few studies on forced and mixed convective heat transfer of nanofluids past circular ( [15][16][17][18]) and square ( [19][20]) cylinders have recently been reported, a systematic study addressing this extremely significant issue is yet to be found in the literature.…”
Section: Introductionmentioning
confidence: 99%